Pemanfaatan Model Pembelajaran Modifikasi Numbered Head Together dalam Meningkatkan Prestasi Belajar IPA Siswa Kelas IX - Suharno (IBTIDA’, 2023)
It is hoped that this research will succeed in improving learning seen from the teacher and student dimensions by implementing or using a relatively new Natural Sciences learning approach, namely the Modified Numbered Head Together approach, for the subject of the Impact of Biotechnology Application and Development. This research uses a Classroom Action research plan. This research was carried out on 32 students in class IX-B even semester at SMP Negeri 1 Sekaran, Lamongan Regency for the 2022/2023 academic year. This research design model has two cycles. Each cycle consists of four stages, namely: action plan preparation stage, action implementation stage, observation stage, and reflection stage. In Cycle I, the average student score was 66.56 with the lowest score being 60 and the highest score being 80. The number of students who got a score above 60 was 17 students, which means 51% of the 32 students had a score above the level of mastery of the given concept. And in Cycle II, the average student score was 92.66 with the lowest score being 55 and the highest score being 100. Of the number of students who got a score above 60, 1 student had a score above the level of mastery of the given concept. From cycle 2 it can be said that student learning achievement has increased.